ANALISIS KANDUNGAN LOGAM BERAT DAGING KIJING LOKAL (Pilsbryoconcha exilis) DARI PERAIRAN SITU GEDE, BOGOR - Nurjanah Nurjanah; Rodieser Sembiring; Asadatun Abdullah (UII, 2012)
The purpose of this research was to examine the content of heavy metals Hg, Cd, and Pb of small and large clams over a period of two months (May and July). In this study, depuration system was applied in an effort to reduce the content of heavy metals. The study was done with inventorisation of the sample area, analysis of the characteristics of clams, operation of depuration system, and analysis of content of Hg, Cd, and Pb. Clam in Situ Gede waters showed heavy metal content of mercury and cadmium that were not detected in meat during the period of two months (May and July) both in large and small clams. Content of lead in May was higher than in July. The average lead in waters Situ Gede during the two periods amounted to 1.34 ppm in small clams and 1.44 ppm in large clams. Depuration system could reduce Pb contents in small clams 0.0861 ppm after 10 days and 0.1506 ppm after 20 days and in large clam 0.0513 ppm after 10 days and 0,0835 ppm after 20 days.